2018
DOI: 10.3390/nu10020127
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Effects of Isosteviol on Insulin Secretion and Its Inability to Counteract the Impaired β-Cell Function during Gluco-, Lipo-, and Aminoacidotoxicity: Studies In Vitro

Abstract: Isosteviol (ISV), a diterpene molecule, is an isomer of the backbone structure of a group of substances with proven antidiabetic capabilities. The aim of this study was to investigate if ISV elicits dynamic insulin release from pancreatic islets and concomitantly is able to ameliorate gluco-, lipo-, and aminoacidotoxicity in clonal β-cell line (INS-1E) in relation to cell viability and insulin secretion. Isolated mice islets placed into perifusion chambers were perifused with 3.3 mM and 16.7 mM glucose with/wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Our group previously demonstrated that stevioside reduces postprandial blood glucose levels in type 2 diabetic subjects, 4 and suppresses glucose response to a glucose tolerance test, increases insulin secretion, reduces glucagon release and lowers blood pressure in type 2 diabetic Goto-Kakizaki rats. 8,9,13,23 In the present study, we have found that the metabolite, SVG, possesses the same properties. When supplemented to soy-based diet, stevioside shows beneficial effects on the development of the metabolic syndrome with hyperglycaemia, hypertension and dyslipidaemia.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Our group previously demonstrated that stevioside reduces postprandial blood glucose levels in type 2 diabetic subjects, 4 and suppresses glucose response to a glucose tolerance test, increases insulin secretion, reduces glucagon release and lowers blood pressure in type 2 diabetic Goto-Kakizaki rats. 8,9,13,23 In the present study, we have found that the metabolite, SVG, possesses the same properties. When supplemented to soy-based diet, stevioside shows beneficial effects on the development of the metabolic syndrome with hyperglycaemia, hypertension and dyslipidaemia.…”
Section: Discussionsupporting
confidence: 68%
“…10,28 Furthermore, we have disclosed that stevioside, rebaudioside A, steviol (steviol glycosides' aglucon) and isosteviol (steviol glycosides' derivative) have the capability to enhance insulin secretion from isolated mouse islets in a dose-and glucose-dependent manner. 8,9,13,23 In the present study, we have found that the metabolite, SVG, possesses the same properties. In static incubation studies, the insulinotropic effect of SVG was present in a broad concentration range, with the maximal effect at 10 −7 mol/L.…”
Section: Effects Of 72-h Exposure To Svg On Gene Transcription In Msupporting
confidence: 68%
See 3 more Smart Citations